Knowledge, attitude and practice toward oral anticoagulants among patients with atrial fibrillation - Li, Chang; Meng, Yubo; Meng, Xiaoping; Song, Yuming (Frontiers in Cardiovascular Medicine, 2023)
Background:Atrial fibrillation (AF) is a common cardiac arrhythmia that increases the risk of stroke and other cardiovascular complications. Oral anticoagulants (OACs) are effective in reducing this risk. To investigate the knowledge, attitude and practice (KAP) toward OACs among patients with AF. Methods:This web-based cross-sectional study was conducted at local Hospital between April 2023 and May 2023, and enrolled AF patients. Results:A total of 491 valid questionnaires were collected, with 293 (59.67%) male and 73.93% resided in urban areas. The KAP scores were 4.64 ± 3.28, 21.09 ± 2.33 and 26.18 ± 2.15, respectively. Multivariate logistic regression analysis showed that junior high school [odd ratio (OR) = 0.346, 95% confidence interval (CI) = 0.145 - 0.825, P = 0.017], junior college/bachelor and above (OR = 6.545, 95% CI = 2.863 – 14.963, P < 0.001), monthly income ≥ 5,000 (OR = 2.343, 95% CI = 1.074 – 5.111, P = 0.032), never taken OACs (OR = 0.015, 95% CI = 0.004 - 0.059, P < 0.001), and having been diagnosed AF (6-10 months, OR = 4.003, 95% CI = 1.653 – 9.692, P = 0.002;over 20 months, OR = 4.046, 95% CI = 1.753 - 9.340, P = 0.001) were independently associated with knowledge. Knowledge (OR = 1.376, 95% CI = 1.162 - 1.629, P < 0.001), junior high school (OR = 0.258, 95% CI = 0.084 - 0.792, P = 0.018), monthly income ≥ 5,000 (OR = 5.486, 95% CI = 1.834 - 16.412, P = 0.002), and never undergone AF ablation (OR = 0.214, 95% CI = 0.097 - 0.471, P < 0.001) were independently associated with attitude. Knowledge (OR = 1.128, 95% CI = 1.030 - 1.235, P = 0.009), 70-79 years (OR = 2.193, 95% CI = 1.166 - 4.124, P = 0.015) and ≥80 years (OR = 4.375, 95% CI = 2.034 - 9.411, P < 0.001) were independently associated with proactive practice. Conclusion:Patients with AF had inadequate knowledge, suboptimal attitude and inactive practice towards AF and OACs. Improving patient education, especially among those with lower education levels, enhances understanding and management of AF and OACs.